Bipolar radio-frequency-induced thermofusion of intestinal tissue – In vivo evaluation of a new fusion technique in an experimental study. (3rd July 2016) - Holmer, Christoph; Winter, Hanno; Nagel, Alexandra; Jaenicke, Annika; Lauster, Roland; Kraft, Marc; Buhr, Heinz. J.; Ritz, Jörg-Peter; Zickerow, Matthias
Abstract: Purpose: Bipolar radio-frequency-induced thermofusion (BiRTh) of intestinal tissue might replace conventional stapling devices which are associated with technical and functional complications. Previous results of our study group confirmed the feasibility to fuse intestinal tissue using BiRTh-induced thermofusion ex vivo. The aim of this study was now to evaluate the efficacy of fusing intestinal tissue in vivo by BiRTh-induced thermofusion. Materials and methods: In male Wistar rats a blind bowel originating from the caecum was closed either by BiRTh (n = 24) or conventional suture (n = 16). At 6 h, 48 h, 4 days, and 2 weeks after the procedure caecum bursting pressure was measured to compare both groups. Results: In total 18 of 21 (85.7%) thermofused and 15 of 16 (93.7%) sutured cecal stumps were primarily tight and leakage-proof ( p > 0.05). The operative time was comparable in both groups without significant differences. Both groups showed increases in bursting pressure over the post-operative period. The mean bursting pressure for thermofusion was 47.8, 48.3, 55.2, and 68.0 mmHg, compared to 69.8, 51.5, 70.0 and 71.0 mmHg in the hand-sutured group ( p  > 0.05) after 6 h, 48 h, 4 days, and 2 weeks, respectively. Conclusion: These results suggest that BiRTh-induced thermofusion is a safe and feasible method for fusing intestinal tissue in this experimental in vivo model and could be an innovative approach for achieving gastrointestinal anastomoses.